Flexibility-Rigidity Coordination of the Dense Exopolysaccharide Matrix in Terrestrial Cyanobacteria Acclimated to Periodic Desiccation - Liu, Wen (Appl Environ Microbiol, 2017)
A dense exopolysaccharide (EPS) matrix is crucial for cyanobacterial survival in terrestrial xeric environments, in which cyanobacteria undergo frequent expansion and shrinkage processes during environmental desiccation-rehydration cycles. However, it is unclear how terrestrial cyanobacteria coordinate the structural dynamics of the EPS matrix upon expansion and shrinkage to avoid potential mechanical stress while benefiting from the matrix. In the present study, we sought to answer this question by investigating the gene expression, protein dynamics, enzymatic characteristics, and biological roles of WspA, an abundantly secreted protein, in the representative terrestrial cyanobacterium Nostoc flagelliforme. The results demonstrated that WspA is a novel β-galactosidase that facilitates softening of the EPS matrix by breaking the polysaccharide backbone under substantial moisture or facilitates the thickening and relinkage of the broken matrix during the drying process, and thus these regulations are well correlated with moisture availability or desiccation-rehydration cycles. This coordination of flexibility and rigidity of the cyanobacterial extracellular matrix may contribute to a favorable balance of cell growth and stress resistance in xeric environments. IMPORTANCE How the exopolysaccharide matrix is dynamically coordinated by exoproteins to cope with frequent expansion and shrinkage processes in terrestrial colonial cyanobacteria remains unclear. Here we elucidated the biochemical identity and biological roles of a dominant exoprotein in these regulation processes. Our study thus gained insight into this regulative mechanism in cyanobacteria to combat periodic desiccation. In addition, the filamentous drought-adapted cyanobacterium Nostoc flagelliforme serves as an ideal model for us to explore this issue in this study.